Houses of worship as restorative environments - Hasbullah, Muhammad Faris Syahmi; Ahmad, Izzat Firdaus; Sukeri, Mohd Shuib; Zulkarnain, Nurul Kamal; Mohd Mahudin, Nor Diana (Kulliyyah of Architecture and Environmental Design, IIUM, 2013)
Despite the established role of houses of worship in restoring individuals from stress and mental fatigue, there is insufficient research on this issue, particularly in Malaysia, which, in turn, warrants a closer examination of existing scientific endeavour and corresponding evidence. A cross-sectional comparative survey using questionnaires was employed to 89 participants (Muslims = 54; Christians = 35) from a church and a mosque to address two objectives: to identify the relationship between moods before and after visiting these houses of worship and to investigate the motivations for visiting these places. Data were analysed by Pearson’s correlation and independent sample t-test. Results indicate that there is a significant relationship between moods before and after visiting the houses of worship. Findings also demonstrate that there is a statistically significant difference in motivation levels between masjid visitors and church visitors. Overall, the findings suggest that a house of worship can provide an avenue for the visitors for fulfilling their spiritual needs and rejuvenating their mood as well as restoring their directive attention.